Abdominal ultrasound in the evaluation of fibrosis and portal hypertension in an area of schistosomiasis low endemicity - Espírito Santo, Maria Cristina Carvalho do; Azeredo, Letícia Martins; Teles, Horácio Manuel Santana; Gryschek, Ronaldo Cesar Borges; Ferreira, Cláudio Santos; Amato Neto, Vicente (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
This study was undertaken in the municipality of Bananal, São Paulo, an endemic area for schistosomiasis with a prevalence under 10% and low parasite load among infected individuals. Our objective was to identify the clinical forms of schistosomiasis among 109 patients in whom the disease had been diagnosed through direct fecal analysis and who had been medicated with oxamniquine at the time of the Plan for the Intensification of Schistosomiasis Control Actions (1998-2000). These patients were submitted to an abdominal ultrasonography and fecal analysis by Kato-Katz method, four years, on average, after the end of the Plan. Five patients, whose abdominal ultrasound images were compatible with either peripheral or central periportal fibrosis and portal hypertension, were identified. None of the 109 patients presented Schistosoma mansoni eggs at fecal analysis. Ultrasonography is a sensitive, noninvasive diagnostic method that allows a better identification of the extent of liver involvement in schistosomiasis cases.